Risk factors for acute pancreatitis in patients with severe motor and intellectual disabilities. Issue 2 (29th January 2014) - Tamasaki, Akiko; Nishimura, Yoko; Kondo, Noriko; Shirai, Kentaro; Maegaki, Yoshihiro; Ohno, Kousaku
Abstract Background Acute pancreatitis in patients with severe motor and intellectual disability (SMID) is a rare but life‐threatening condition. Possible causes of acute pancreatitis in these patients including valproic acid therapy, hypothermia and nasoduodenal tube feeding, have not yet been investigated in detail. The aim of this study was therefore to investigate the risk factors for acute pancreatitis in patients with SMID. Methods Five SMID patients with acute pancreatitis and 15 SMID patients without acute pancreatitis were reviewed. Age; serum total cholesterol, triglyceride, total protein, and albumin; height; bodyweight; body surface area; body mass index; daily calorie intake; daily calorie intake per unit of body mass surface area; daily calorie intake per kilogram bodyweight; and valproic acid usage were examined. Results A statistically significant difference was observed in serum albumin level between the two groups (P = 0.026). Conclusion The mechanism of acute pancreatitis in these patients was considered as pancreatic morphological change, acinar damage, and elevated serum trypsinogen level caused by malnutrition. It is likely that acute pancreatitis in patients with SMID occurs due to the same mechanism as in anorexia nervosa and malnourished patients. To prevent acute pancreatitis in these patients, it is important to maintain adequate nutritional status.